Application of Grummons Analysis for the Three-dimensional Facial Asymmetry Assessment - Sandhra T. Madhu; Rahul D. Prabha; N. K. Sapna Varma; V. V. Ajith (Contemporary Clinical Dentistry)
Background: The assessment of three-dimensional (3D) Grummons analysis of cone-beam computed tomography (CBCT) and computed tomography (CT) using Dolphin Software in comparison to conventional manual tracing technique using two-dimensional (2D) postero-anterior (PA) cephalogram has been evaluated in this study. Materials and Methods: Pretreatment records of patients who underwent CBCT (n = 23) or CT (n = 23) scan were collected. 3D Grummons analysis of the CBCT and CT images were performed on Dolphin 11.9. In addition, PA cephalograms were reconstructed from these 3D data and Grummons 2D analysis was performed. The 2D PA cephalograms obtained were then printed on X-ray films for manual tracing. Intrarater correlation coefficient was calculated for assessing the reliability of the values obtained using 3D, 2D, and manual tracings and paired t test was used to test the significance of mean values. Results: The results from the comparison of 3D and 2D data analysis indicated inconsistencies in anteroposterior parameters, particularly evident when CBCT and CT. The results from CBCT measurements showed the highest reliability when comparing 3D with 2D (both digital and manual tracings). Moderate-to-good reliability was found in CT measurements at Co-MSR (right and left), J-MSR right, mx/m and midline deviation, Me-deviation, Co-Ag (right and left) when comparing 3D and 2D methods. Paired t-test showed significant difference (P < 0.05) in the measurements comparing between Dolphin 3D and manual using CBCT at Ag-MSR left, Co-MSR (right and left), J-MSR (right and left). Among the CT measurements obtained, Dolphin 3D versus 2D and 2D manual tracing was found to show significant difference in parameters; Co-MSR right, Co-MSR left, J-MSR left, Co-MSR left, Ag-Me right, Ag-Me left Co-Ag right, and L6-MSR left. Conclusions: The study results prove that the use of a single CBCT minimizes the radiation exposure as well as delivers a more accurate representation of 3D anatomical structures.